Biomechanical feedback and feedforward responses during perturbed running in asymptomatic individuals - Khajooei, Mina; Quarmby, Andrew; Mayer, Frank; Engel, Tilman (Frontiers in Sports and Active Living, 2024)
Assessment of biomechanical features whilst running on an uneven terrain plays an important role in identifying running-related injury mechanisms. However, feedback and feedforward motor responses and adaptations, an important component of gait retraining and injury rehabilitation programs, have been less investigated during running. Therefore, the current study assessed the whole-session responses and within-session adaptation mechanisms during perturbed running. Twenty three individuals performed an eight-minute perturbed treadmill running protocol with one-sided decelerative belt perturbations. Joint angle curves and muscle activity amplitudes were analysed throughout the running cycle, in both the perturbed and contralateral leg. For the whole-session responses, the average of 10 consecutive strides during the baseline trial and all perturbed strides from the perturbed running trial were compared. To assess within-session adaptation, the first perturbation was compared to the average of the last three perturbations. Data were analysed with one-dimensional statistical parametric mapping of Paired t-tests to assess responses and adaptations to the perturbations (P < 0.025). Regarding whole-session responses (baseline vs. perturbations), statistically significant feedback (after perturbation) responses were detected in most measured joint angles and muscle activity of both perturbed and contralateral legs. Feedforward (before perturbation) responses for whole-session comparison were detected for most joint angles in the contralateral leg and only hip flexion in the perturbed leg. Feedforward muscle activities of whole-session responses were different in the biceps femoris, semitendinosus, and erector spinae of the perturbed leg, and the soleus of the contralateral leg. Regarding within-session (first vs. last three perturbations) adaptation, feedback adaptations included statistically significant changes in ankle, knee, and hip movements, and muscle activities in the perturbed leg, while the contralateral leg showed less adaptation. No significant feedforward within-session adaptations were observed in the perturbed leg, but the contralateral leg showed changes in ankle dorsiflexion, soleus activity, and erector spinae activity. Findings suggest that participants compensated perturbations during running by modifying muscle activities and movement patterns, primarily through feedback mechanisms in the perturbed leg, with limited feedforward adaptations. The current protocol may present a viable approach for testing and training postural control during running.